2015
DOI: 10.15580/gjas.2015.5.082415121
|View full text |Cite
|
Sign up to set email alerts
|

Dichotomous key determining varietal groups of yam species Dioscorea alata L.

Abstract: Yam is an important food crop in Côte d'Ivoire. Nevertheless, its production is facing many constraints including the inability to distinguish cultivated varieties from one another. Thus, different varieties and species are designated by the same names from one region to the other and vice versa, the same varieties are called differently. The absence of major descriptors, which are easy to use is the main cause of this confusion. The objective of this study is to propose agro-morphological descriptors easy to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…However, field trials for C18 showed that it yielded less than other alata clones, which had not been widely grown. This difference confirmed the importance of culinary quality in adoption (Kouakou et al, 2012). As (Doumbia et al, 2014) notes, by 2007 in the central region of Côte d'Ivoire" the average coverage per farm was as follows: C18 covered 0.17 ha, Florido 0.12 ha, all D. Alata (0.32 ha), and all yams (D. alata and rotundata) 0.35 ha.…”
Section: Yam In Côte D'ivoirementioning
confidence: 73%
“…However, field trials for C18 showed that it yielded less than other alata clones, which had not been widely grown. This difference confirmed the importance of culinary quality in adoption (Kouakou et al, 2012). As (Doumbia et al, 2014) notes, by 2007 in the central region of Côte d'Ivoire" the average coverage per farm was as follows: C18 covered 0.17 ha, Florido 0.12 ha, all D. Alata (0.32 ha), and all yams (D. alata and rotundata) 0.35 ha.…”
Section: Yam In Côte D'ivoirementioning
confidence: 73%
“…For example, the improved varieties C18 and Florido are called Cameroun or Americain by the farmers. The works of Kouakou (2010) and Kouakou et al (2015) gave agro-morphological criteria for the identification of varietal groups for D. alata.…”
Section: Discussionmentioning
confidence: 99%